The Role of Nicotinamide Adenine Dinucleotide Phosphate Oxidase-Derived Reactive Oxygen Species in the Acquisition of Metastatic Ability of Tumor Cells - Okada, Futoshi (American Society for Investigative Pathology, 2006)
We examined the role of phagocyte-derived oxygen radicals in tumor cell acquisition of metastatic phenotype by comparing gp91(phox−/−) mice and C57BL/6J wild-type (WT) mice. The gp91(phox−/−) mouse is deficient in the gp91(phox) gene, an essential subunit of the phagocyte nicotinamide adenine dinucleotide phosphate oxidase that generates superoxide anion. QR-32 fibrosarcoma cells are nonmetastatic but are converted into metastatic tumors once in contact with foreign body (gelatin sponge)-induced phagocytes in vivo. Compared to QR-32 cells co-implanted with the foreign body in WT mice, those in gp91(phox−/−) mice exhibited reduced metastasis. There was no difference in the incidence of primary tumors after injection of B16BL6 melanoma cells in WT and gp91(phox−/−) mice. However, after resection of the primary tumors, metastases were reduced in gp91(phox−/−) mice. Thymosin β4 gene expression and cell motility/invasion were seen in the tumors from WT mice but not in those from gp91(phox−/−) mice. Adoptive transfer of phagocytes from WT mice, but not those from gp91(phox−/−) mice, restored the metastatic ability of tumors grown in gp91(phox−/−) mice. These findings show that tumor metastatic behavior can primarily be endowed by phagocyte-derived superoxide anion and its oxidative metabolites, which are generated through activation of nicotinamide adenine dinucleotide phosphate oxidase.